PENINGKATAN KOMPETENSI MENYUSUN KERANGKA PENELITIAN TINDAKAN BIMBINGAN DAN KONSELING DI MGBK SMP/MTs KABUPATEN PEKALONGAN - Sukoco Kasidjan Wirjosoehardjo; Hanung Sudibyo; Muhammad Arif Budiman (Bagimu Negeri, 2017)
Guidance and counseling teachers need training on the preparation of action research guidance and counseling. Is the guidance and counseling teacher is able to frame the action research guidance and counseling? Methods include seminars and training developed the framework for action research guidance and counseling. The result of the process of obtaining training 32 participants who understands and is able to frame the action research guidance and counseling, while six participants have not been able to frame the action research guidance and counseling correctly.Keywords : Action Research; Competence; Guidance and Counseling